Jasa Antar Barang (Secepat) Impor Baju (Perbal) Dari Pelabuhan Tanjung Priuk Ke Consigne Dan Menjual Baju Impor Ke UMKM - Nabila Aprilia; Elsa Octavia Simangunsong; Yogi Saputra; Bayu Nurcahyo (Journal Of Business, Finance, and Economics (JBFE), 2023)
Competition in business between goods services or commonly known as Sicepat from this port is not well known among the public because to enter the port using E-money and also requires more than one person due to transporting goods that are quite large from the goods down from the ship down to the in the car. This business is quite helpful for people who need goods delivery services because the way to order this service is still through the WhatsApp application and ordering manually. Basically this business helps people who routinely need delivery services because this delivery service business is quite affordable in terms of costs, it is cheaper than other shuttle businesses. And besides the goods delivery service business, it also sells clothing in large quantities to MSMEs or partners. those who cooperate with our business and those who do not cooperate. Provide clothing that is needed or that is being sought.